Affective consequences of optimism and pessimism in the face of failure: Evidence of a moderation by attribution. (September 2015) - Lau, Stephan; Naujokat, Mariane; Kubiak, Thomas
Highlights: We disentangled the effects of dispositional optimism and attributions on affect. We measured feelings of success and feelings of failure. Participants experienced a failure, attributing it to themselves or a teammate. Feelings of optimists were greatly affected by the attribution. Attribution had no effect on the feelings of pessimists. Abstract: The present experiment set out to investigate the affective consequences of dispositional optimism and attribution in performance settings. Optimistic and pessimistic participants ( N  = 42 each) experienced failure at solving two cognitive tasks in an alleged team setting. The failure could either be attributed to themselves (internal condition) or a teammate (external condition). We found disordinal interactions of optimism and attribution on the feelings of success and feelings of failure. While the affective state of optimists deteriorated significantly if they attributed the failure internally compared to externally, pessimists were emotionally unaffected by the locus of attribution. Moreover, optimists experienced affective benefits compared to pessimists when they attributed the outcome externally. The reverse was true if they had attributed internally. Affective consequences of optimism and pessimism after failure therefore seem to differ depending on attributions. Furthermore, pessimists seemed to be unresponsive to the affective effects of attribution in our study. This insensitiveness implies differences in the cognitive processing of outcomes, a trait × cognition interaction that should be investigated further.